1. Wykonaj działania :
a) 6(x-4)- 2=
b) 2(x+1)- 3(x+1)=
c) -3(y-2) + 4(y+2) =
d) 5(x-y-1) - 4(x+2)=
e) 2(3a + b) - 2(a- b )=
f) ½(4x - 4) - 2x =
g) x(x-1) - 3(x² - x)=
h) 5a(a-3) - 3a(a-5)=
i) 3x(x+⅓ y ) - 2y (½x - ½)=

2.Uprość podane wyrażenie :
4 * (x-7) :2 + 9 * (x-1) : 3 =

z.3 Wyłącz wspólny czynnik przed nawias :
a) 5x + 10y =
b) 4m + 4 =
c) 3a- 3 =
d) 5xy - x =
e) -6a² - 2a =
f) 6a² - 12ab =
g) ½ xy - ½x =
h) ⅓ a²b + 1/9ab² =
i) 2xyz - 4x²y²z + xyz² =
j) stv² - stv + tv² =
* 1/9 = jedna dziewiąta
-----------
z. 4 Zapisz w postaci iloczynu :
a) ½ * 4(a+b) - ½h(a+b) =
b) z(x-y)-(y-x) =
PROSZE TO NA JUTRO . DAM NAJ :))

1

Odpowiedzi

2010-03-10T15:43:48+01:00
1.
a)6(x-4)-2=6x-24-2=6x-22
b)2(x+1)-3(x+1)=2x+2-3x-3=-x-1
c)-3(y-2)+4(y+2)=-3y+6+4y+6=y+12
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a=4b
f)½(4x-4)-2x=2x-2-2x=-2
g) x(x-1) - 3(x² - x)=x²-x-3x²+3x
h)5a(a-3) - 3a(a-5)=5a²-15a-3a²+15a=2a²
i)3x(x+⅓ y ) - 2y (½x - ½)=3x²+xy-xy+y=3x²+y

2.
4 * (x-7) :2 + 9 * (x-1) : 3 = (4x-28):2+(9x-9):3=2x-14+3x-3=5x-17

3.
a) 5x + 10y =5(x+2y)
b) 4m + 4 = 4(m+1)
c) 3a- 3 = 3(a-1)
d) 5xy - x = 5x(y-1)
e) -6a² - 2a = 2a(-3a-1)
f) 6a² - 12ab = 6a(a-2b)
g) ½ xy - ½x = ½ x(y-1)
h) ⅓ a²b + 1/9ab² =⅓a(ab+⅓b²)
i) 2xyz - 4x²y²z + xyz² = xyz(2-4xy+z)
j) stv² - stv + tv² = tv(sv-s+v)

4.
a) ½ * 4(a+b) - ½h(a+b) = ½ *(4a+4b)-½ha+½hb=2a+2b-½ha+½hb
b) z(x-y)-(y-x) = zx-zy-y+x



15 3 15